A Novel Campylobacter apparatus for the detection of viable thermophilic Campylobacter in chicken meat products - Sueptrakool Wisessimbat (Prince of Songkla University, 2011)
Thesis (Ph.D., Microbiology)--Prince of Songkla University, 2009